In Silico Study of Bioactive Compounds Fucoxanthin and Fucoidan from Sargassum echinocarpum as Anti-Cancer Agents Targeting Caspase-3 Protein - Mualimin, Lulus; Arum, Mentari Sekar (Aquatic Life Sciences, 2025)
Cancer is a complex disease characterized by disruptions in cell regulation mechanisms, leading to abnormal or uncontrolled cell growth and the ability to spread to other parts of the body. The caspase-3 protein plays a crucial role in the apoptotic mechanism and is a key target in cancer therapy. Bioactive compounds from the brown alga Sargassum, such as fucoidan and fucoxanthin, show significant potential as anticancer agents through mechanisms including apoptosis induction, cell cycle arrest, and metastasis inhibition. This study employed an in silico method to investigate the interaction between the natural ligands fucoidan and fucoxanthin and the target protein caspase-3, simulating their potential as anticancer drug candidates. The analysis revealed distinct interactions for each ligand with the target protein, as indicated by their binding affinity values. The interaction between fucoidan and caspase-3 resulted in a binding affinity value of ∆G -4.7 kcal/mol, which was lower in effectiveness compared to the interaction between fucoxanthin and caspase-3, with a binding affinity value of ∆G -7.7 kcal/mol. This suggests that fucoxanthin exhibits stronger anticancer activity through its interaction with caspase-3 compared to fucoidan. Meanwhile, toxicity tests showed that fucoidan has a lower toxicity profile than fucoxanthin, particularly in terms of LD₅₀ values and active/inactive toxicity parameters. These findings indicate that fucoxanthin has potential as anticancer drug candidates. Further research is needed to optimize their therapeutic efficacy and safety profiles.